2002
DOI: 10.1002/bdm.420
|View full text |Cite
|
Sign up to set email alerts
|

The impact of affective information on the professional judgments of more experienced and less experienced auditors

Abstract: This study examines whether the presence of realistic, yet irrelevant, affective information differentially influences the professional judgments of more experienced and less experienced auditors. In this study, auditors with different experience levels were either provided or not provided with information designed to elicit a negative interpersonal emotional reaction towards a manufacturing client when making an inventory obsolescence risk judgment. The results indicate that the inventory obsolescence risk as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 58 publications
(70 reference statements)
4
68
0
3
Order By: Relevance
“…I also provide several findings that contribute to an emerging body of research that suggests affect can influence auditor judgment ͑Chung et Schafer 2007;Curtis 2006;Bhattacharjee and Moreno 2002͒. While prior research has examined interpersonal affect based on the personality of the client, I extend this research by providing evidence that a client can strategically induce interpersonal affect.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…I also provide several findings that contribute to an emerging body of research that suggests affect can influence auditor judgment ͑Chung et Schafer 2007;Curtis 2006;Bhattacharjee and Moreno 2002͒. While prior research has examined interpersonal affect based on the personality of the client, I extend this research by providing evidence that a client can strategically induce interpersonal affect.…”
Section: Discussionmentioning
confidence: 89%
“…First, I find that auditors are more likely to comply with client requests as positive affect toward the client increases. This result extends prior research by examining a setting in which the client strategically induces affect rather than a setting in which affect is based on the personality of the client ͑e.g., Bhattacharjee and Moreno 2002͒. Second, auditors felt stronger positive affect toward the ingratiating client than the non-ingratiating client.…”
Section: Introductionmentioning
confidence: 95%
“…Bhattacharjee and Moreno (2002) found that negative affective client information significantly influenced less-experienced auditors' judgments. Bhattacharjee and Moreno (2002) found that negative affective client information significantly influenced less-experienced auditors' judgments.…”
Section: Affect and Emotionsmentioning
confidence: 91%
“…Until recently, this aspect of human behavior has been overlooked by accounting researchers. Recent accounting research has begun to examine affective states and has focused on emotions and evaluations ͑e.g., Bhattacharjee and Moreno 2002;Moreno et al 2002;Kadous 2001;Kida et al 2001͒. This study builds on prior accounting and psychology research by focusing on how audit judgment is influenced by moods.…”
Section: Introductionmentioning
confidence: 98%